High speed 4D printing of shape memory polymers with nanosilica - Choong, Yu Ying Clarrisa (2020)
This work presents a novel development to accelerate the printing speed of photopolymerization-based process by improving resin curability with nanosilica fillers. The nanosilica particles are revealed as “superior catalysts” that altered the light scattering characteristics of the resin. By taking advantage of the large number of compact nucleation sites on their surfaces, the nanosilica facilitated remarkably fast curing rates by greatly reducing the curing time for each layer of printing from 4 s to 0.7 s. The addition of nanosilica into shape memory polymers (SMPs) resins has also invoked new development of SMP composites as reinforced 4D printing materials. The particle-polymer interaction was carefully tuned to control the plasticizing effect of nanosilica domains in the polymer chains. The printed composites exhibited improvement in mechanical properties by an order of magnitude and greater elongation of 85.2 % as compared to their neat SMPs. The multifunctional crosslink nature of the nanosilica also maintained the shape recovery ratio within a high range of 87–90%. This work achieves fresh mechanistic insights in the critical role and influences of nanosilica in developing high speed 3D printing technology and opens up newly-developed high-performance material.